DESIGN OF TOURIST BEACH RESORT IN TANJUNG KARANG DONGGALA, CENTRAL OF SULAWESI - ARIEF (nim : 25212033), IRDINAL
Central Sulawesi province has a pretty beach tourism potential of attracting the attention of tourists, among them are the white sand beaches, sunset, tropical beach forest, as well as the beauty of the seabed especially coral reefs located in Tanjung Karang Donggala. Natural conditions are mostly tourist destinations are still awake, but there are also some that are less well preserved due to the exploitation of tourists and locals. As well as the layout of the building exceeded the borders of the coast, increasing garbage in the coastal area even to the sea, the excessive consumption of clean water and waste water disposal which are not directional and uncontrolled. So komsumsi reduction strategies need to be excessive energy by making use of the surrounding environment. This energy consumption reduction strategies will be applied with a biomimetic approach on the building of the resort come within this tour, with the hope it can reduce the consumption in addition to the lowliest energy tour, could also bolster the economy of the local community. Biomimetic approach in the design of sustainable architecture is one of the models offered a human to sustain their existence in advance of the Earth in a way to minimize the damage to nature and the environment in the region. Because essentially it is a building with a significant energy consumption then the need for efforts to minimize energy consumption by loading the environment around sustainability strategy that consists of natural and artificial environments. The strategy of sustainability in the integration between the resort and the surrounding nature of biomimetic architecture, which includes climate, biology, Architecture and technology. The study only covers how to follow or imitate nature surrounding Tanjung Karang it by looking at the initial conditions, good climatic conditions and existing technologies, in this case the adaptation and evolution is adaptation and evolution of the culture of the surrounding environment. With the concept and method of building of this kind, the exploitation of nature will be minimised and realized buildings tend to be in harmony with nature. The climate here is management utilization of some energy from the quality of the local climate, such as the utilization of energy from the Sun, wind and water is sourced from natural surroundings, as well as adopt local tradition as langgam building done by mimetik (process mimics), with the transformation are relevant. Biomimetic approach in this discussion is not done in depth, but limited to a simple simulation, including site management, site analysis through the interaction of environmental, architectural design concepts of traditional architecture as building style, the shape of the building mass, and management of renewable energy partly schematically.